FAM136A immunoreactivity is associated with nodal involvement and survival in lung adenocarcinoma in a Chinese case series. Issue 1 (1st January 2020) - Zhao, Liufang; Ge, Chunlei; Zhang, Zhiwei; Hu, Hongyan; Zhang, Yi; Zhao, Wentao; Li, Ruilei; Zeng, Baozhen; Song, Xin; Li, Gaofeng
ABSTRACT: Lung cancer patients with lymph node metastasis usually had short overall survival and occurred distant metastases at the early stage. However, some of these people did have more prolonged survival. The underlying reason is still unclear. In this study, we found a novel molecule, family with sequence similarity 136, member A gene (FAM136A). First, we performed immunohistochemistry for FAM136A in 177 lung carcinoma tissues. Second, we carried out in vitro studies by using A549 and PC-9. We detected FAM136A immunoreactivity in 79 out of 177 (44.6%) lung carcinoma tissues, and the FAM136A status was significantly associated with tumor T stage, lymph node metastasis, and the Tumor-Node-Metastasis (TNM) staging system in these cases. Importantly, it was significantly associated with the overall survival of the patients with lymph node metastasis, especially FAM136A positive patients, who had worse outcomes. Subsequent in vitro experiments revealed that the proliferation activity and migration property decreased both A549 and PC-9 lung carcinoma cells transfected with siRNA-FAM136A, and apoptosis reduced. Meanwhile, the expression of CDK4 and CDK6 decreased. FAM136A status would be a potent, worse prognostic factor in lung cancer patients with lymph node metastasis. It would play a vital role in the proliferation, apoptosis, and migration properties of A549 and PC-9. In the future, We will focus on the uncovered signal mechanism between FAM136A and lung cancer. Graphical abstract: Abbreviation: FAM136A: family with sequence similarity 136 member A; NSCLC: non-small-cell lung cancer; SCC: squamous cell carcinoma; IHC: immunohistochemistry; PBS: phosphate-buffered saline; CDK: cyclin-dependent kinase.